Calculation of the apparent Michaelis constant for biosensors using reaction-diffusion equations - Katauskis, Pranas; Ivanauskas, Feliksas; Laukevičius, Sigitas (Lietuvos matematikos rinkinys, 2014)
The relationship between the apparent Michaelis constant and the diffusion module for one and two-layer biosensors is studied using a mathematical model describing action of the amperometric biosensors.